1970
DOI: 10.3329/dujps.v7i1.1201
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective Effects of <i>Thespesia lampas</i> Dalz & Gibs in CCl<sub>4</sub> Induced Liver Injury in Rats

Abstract: ABSTRACT:The extracts of the roots of Thespesia lampas (Malvaceae) were evaluated for hepatoprotective activity in rats by inducing chronic liver damage by subcutaneous injection of 50% v/v carbon tetrachloride in Tween 80 at a dose of 3ml/kg for a period of 4 weeks. The biochemical parameters like serum glutamate pyruvate transaminase (SGPT), serum glutamate oxaloacetate transaminase (SGOT), alkaline phosphatase (ALP), serum bilirubin and total proteins were estimated to assess the liver function. Hepatic ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 5 publications
(1 reference statement)
0
4
0
Order By: Relevance
“…In that study, the water extract of the plant root was reported to have more hepatoprotective activity than the methanol extract. [8] In this study, the ethanol extract was found to be better than the water extract.…”
mentioning
confidence: 73%
“…In that study, the water extract of the plant root was reported to have more hepatoprotective activity than the methanol extract. [8] In this study, the ethanol extract was found to be better than the water extract.…”
mentioning
confidence: 73%
“…The nitric oxide radical scavenging capacity of the fractions was measured by Griess reaction, following Sangermeswaran et al [13]. Ascorbic acid was used as the reference standard.…”
Section: Nitric Oxide Radical Scavengingmentioning
confidence: 99%
“…Thespesia lampas is not a well-known ethnomedical medicinal plant. The plant has been reported for various therapeutic properties including hepatoprotective ( Ambrose et al, 2012 ), antioxidant ( Sangameswaran et al, 2009 ), anthelmintic ( Kosalge and Fursule, 2009 ), anti-diabetic ( Jayakar and Sangameswaran, 2008 ), and antimicrobial studies ( Valsaraj et al, 1997 ). The root, stem, and leaves have been reported for anti-inflammatory, anthelmintic acidity, bleeding nose, bronchitis, carbuncle, cough, dysentery, fever, gonorrhea, sunstroke, and urinary complaints ( Adhikari et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%